Issues of Textile Industry Development in Uzbekistan: Isu Pengembangan Industri Tekstil di Uzbekistan - H.M, Abdunazarov; H.M, Niyozov (Indonesian Journal of Innovation Studies, 2022)
This article covers the reforms implemented in the Republic of Uzbekistan in the years of independence for the development of the textile industry, as well as the issues of the development of the textile industry.